5x/6-2x-1/3=4/5

Simple and best practice solution for 5x/6-2x-1/3=4/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x/6-2x-1/3=4/5 equation:


x in (-oo:+oo)

(5*x)/6-(2*x)-(1/3) = 4/5 // - 4/5

(5*x)/6-(2*x)-(1/3)-(4/5) = 0

(5*x)/6-2*x-1/3-4/5 = 0

-7/6*x-17/15 = 0 // + 17/15

-7/6*x = 17/15 // : -7/6

x = 17/15/(-7/6)

x = -34/35

x = -34/35

See similar equations:

| 4(n-3)+5n+8= | | 9(7c-6)=17-3c | | x-1/7=20/7 | | 9y-7y=32 | | (4z-5)(9+z)=0 | | -6=-5+h | | 5-4y=7 | | 7x+5x-20=80-8x | | 35=-5b | | 3*abs(x-2)=10 | | (56-98-12)*(5*22)= | | -13=d+5 | | -1*(-2)=1 | | 26-3a=-4(9a-5) | | -7=4+c | | 4b+15-6b-9=8-20 | | 3v+9-5=-31 | | (x-1)+(x-1)=3x-7 | | -7-5(1+9k)=30 | | 3/5+12=6 | | 17k-23=6k-13 | | (19b-6)-9(2b+3)=-3 | | Y=15.00+0.75x | | -2000000-80000x=-4400000 | | z-8=-1 | | -9(8h-5)=-29 | | -3(6p+3)-2(2-17p)=3(9+5p) | | (1/8X)-(5/6)=X-(3/4) | | 5a+a+5= | | n+4+4n=11 | | -5a+8-6a=35 | | -6(8+3k)=-16 |

Equations solver categories